Analisis Penerapan Green Economy Melalui Kewirausahaan Berbasis Lingkungan (Ecopreneurship) di SMA YPPK St.Yoanes XXIII Merauke - Prima Lestari Situmorang; Acep Fatchuroji; Juli Arianti; Mutiya Oktariani (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
Environmental damage is threatening the survival of every living thing at this time. Educational institutions created educated, trained, have a strong spirit and still care about the environment. In this case, the school becomes a strategic vessel to form a spirit of environmental concern so that it can overcome environmental problems in the future. One way is through the application of a green economy . This study aims to obtain information on how to implement a green economy through Ecopreneurship at SMA YPPK St.Yoanes XXIII Merauke. This qualitative descriptive. Data collection techniques were carried out through direct observation and interviews with teachers and principals of SMA YPPK St. Yoanes XXIII Merauke. The data obtained were then processed using the Miles and Huberman analysis techniques. The study result stated that the school empowered an environmentally sound entrepreneurial community consisting of teachers and students and continued to develop locally processed products, one of which was lamtoro coffee. It comes from lamtoro seeds. 50% and 50% theory in which the success of learning is measured through understanding the material, an entrepreneurial spirit that cares about the environment, and making business plans that produce new products using the Reuse, Reduce, Recycle, and Upcycle methods.